INVENTARISASI GULMA PADA TANAMAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) DI BALAI PENGAWASAN DAN SERTIFIKASI BENIH PERKEBUNAN - Herry Iswahyudi; Muhammad Fachrurazi (Program Studi Budidaya Tanaman Perkebunan, Politeknik Hasnur, 2021)
Weeds have a direct influence on the growth and yield of oil palm production, resulting in various losses. Weed control aims to suppress growth or destroy weeds in plantations. In order to reduce the risk of failure in weed control, weed inventory activities need to be carried out first. Weed inventory is an activity to collect data on the types of weeds, and is expected to reveal potential and information about weeds. The purpose of this study was to identify and recognize the diversity of weed species that can be used as the basis for weed control in the productive phase of oil palm plantations at the Plantation Seed Monitoring and Certification Center. The method used in this study was a descriptive qualitative approach. The results of the study found 2 divisions, 4 classes, 13 orders, 18 families, 22 genera and 22 plant species on oil palm plantations with narrow, broad, and ferns. In general, based on the results of the inventory, broadleaf weeds were more common than narrow leaf weeds and fern weeds.